The construction of victims of defamation in court’s written verdicts - Mahardhika Zifana; Iwa Lukmana; Dadang Sudana (Universitas Pendidikan Indonesia, 2022)
Most countries in the world consider defamation case to be a civil domain. However, Indonesia still classifies defamation as a criminal act. Following the issue of defamation in the Criminal Code, the establishment of the Law Number 11 of 2008 on Electronic Information Transactions has resulted in a more complex situation because it also covers the act of defamation. After the Law came into force in 2009, to 2014, 71 people had been charged in court for alleged defamation. This study is a linguistic study in the context of law to discuss the construction of victims in copies of court decisions on defamation cases. It aims to reveal the representation of victims in the court’s verdict. The data were taken from two copy-texts of court decisions in 2014 and 2015. The texts explaining the position of victims in relation to one of the grounds for judge’s decision. This study used the Fairclough’s (1997) critical discourse analysis framework that features dialectical-relational approaches to map social relations patterns explaining a party's construction in a discourse. The data interpretation and conclusions reveal the reproductions of the logic of parties in the decisions, marginalization of victims, and the establishment of the role and position of victims in defamation discourses by ignoring institutional aspects and powerlessness. Thus, victims are not the center of discourse in the text copies of Indonesian court decisions. In addition, victim is the most important part of the defamation cases since the cases was classified as a criminal complaint.